2022
DOI: 10.1177/15248380221126186
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Parental Adverse Childhood Experiences and Children’s Outcomes: A Scoping Review

Abstract: Adverse childhood experiences (ACEs) are among the leading environmental causes of morbidity and mortality. Extending research on within-generation effects, more recent scholarship has explored between-generation consequences of ACEs. Despite growing interest in the intergenerational effects of parents’ ACEs on children’s outcomes, this line of scholarship has yet to be coalesced into a comprehensive review. The current study is a scoping review on the intergenerational transmission of parental ACEs and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 117 publications
0
22
0
Order By: Relevance
“…Potential factors contributing to the observed association between parent ACEs and adult child’s arrest may include intergenerational transmission of trauma, shared familial risks (eg, genetic propensity for developmental delay, behavioral health challenges, or other factors associated with the development of criminalized behaviors), and structural disadvantage and oppression (eg, racism and social or economic disadvantage) . For example, evidence suggests that parental mental health symptoms can be a consequence of parents’ ACEs, and parental trauma may influence parenting behaviors .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential factors contributing to the observed association between parent ACEs and adult child’s arrest may include intergenerational transmission of trauma, shared familial risks (eg, genetic propensity for developmental delay, behavioral health challenges, or other factors associated with the development of criminalized behaviors), and structural disadvantage and oppression (eg, racism and social or economic disadvantage) . For example, evidence suggests that parental mental health symptoms can be a consequence of parents’ ACEs, and parental trauma may influence parenting behaviors .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve health equity, prevention of ACEs, coupled with dismantling of a carceral system that is racially biased and counterproductive, is an important focus for policymakers. Parental adversity begets later childhood adversity, and it is vital that every child be given the best chance at a healthy start . Early ACE identification can help detect risk, and a timely and effective response to a child’s identified ACE is paramount, as is a societal reorientation toward health equity and valuing the well-being of all children, including through poverty prevention measures such as the Supplemental Nutrition Assistance Program and elimination of the school-to-prison pipeline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, individuals exposed to ACEs may also develop insecure attachment characteristics, implicated in difficulties with interpersonal relationships which would further affect their capacity to provide sensitive, responsive, supportive, and consistent parenting (Bowlby, 1958(Bowlby, , 1969Rowell & Neal-Barnett, 2022). Reviews (Arnold et al, 2023;Rowell & Neal-Barnett, 2022;Zhang et al, 2022) suggest that although several studies have shown a significant mediating effect of maternal parenting on the association between maternal ACEs and offspring mental health outcomes (e.g., Doi,et al, 2021;Delker et al, 2014), other studies fail to observe a mediating effect (e.g., Bödeker et al, 2019;Esteves et al, 2017). Further, the majority of studies examine this the mediating effect of maternal parenting among young children or amongst samples across childhood, with few studies (Plant et al, 2017;Yoon et al, 2019) examining the mediating effect of maternal parenting among adolescents.…”
Section: Maternal Controlling Parentingmentioning
confidence: 99%
“…Parenting and parent-child attachment represent two critical factors in parent-child interaction. In samples of young children, they have been identified as potential mediators of the association between maternal ACEs and child mental health outcomes (Zhang et al, 2022; Rowell & Neal-Barnett, 2022). However, it is unclear whether the effect of these mediators reduces over time or whether they continue to exert influence into adolescence.…”
Section: Introductionmentioning
confidence: 99%